Impact of COVID-19 pandemic on vaccinations in children in a primary health centre in Northern India - Vemprala, Arushi; Vemparala, Rajshekhar; Sundar, Shyam (International Journal Of Community Medicine And Public Health, 2023)
Background: Pandemics and disease outbreaks necessitate the continuation of routine immunization and vaccination for a specific age group along with safety measures for healthcare professionals. India witnessed the COVID-19 pandemic with a drastic rise in the number of cases across the states and union territories in 2020. Routine childhood immunizations suffered mainly because of an overburdened health system coupled with the fear of COVID-19 infection. The present audit is aimed to study the impact of the interventions made to improve routine immunization in the post-COVID-19 period in children in the age group of 0-16 years suitable for immunization under the National Immunization Scheme. Methods: A cross sectional study was conducted by retrieving records in the PHC for the impact of COVID-19 on routine immunizations for vaccine preventable disease in the 0-16 age group. Data were retrieved and collected in a predesigned proforma. Archives of each of the years 2019, 2020, 2021, and 2022 for the month of April. The effect of the interventions for improving vaccine coverage in the rural population was evaluated. Results: A comparison of pre-covid and covid periods showed a significant drop in routine immunization (p=0.007). Higher immunization rates were observed in post covid compared to the COVID period indicating the positive effect of interventions (p=0.0000014) Conclusions: Vaccination rates improved significantly following interventions in the rural population. Health education on safety precautions for COVID-19 and the importance of routine immunization in the pediatric age group has helped to improve vaccination status.